Cinobufagin Exerts Anticancer Activity in Oral Squamous Cell Carcinoma Cells through Downregulation of ANO1 - Sungwoo Jo (MDPI AG, 2021)
Anoctamin1 (ANO1), a calcium-activated chloride channel, is frequently overexpressed in several cancers, including oral squamous cell carcinoma (OSCC). OSCC is a highly aggressive cancer and the most common oral malignancy. ANO1 has been proposed as a potential candidate for targeted anticancer therapy. In this study, we performed a cell-based screening to identify novel regulators leading to the downregulation of ANO1, and discovered cinobufagin, which downregulated ANO1 expression in oral squamous cell carcinoma CAL-27 cells. ANO1 protein levels were significantly reduced by cinobufagin in a dose-dependent manner with an IC50 value of ~26 nM. Unlike previous ANO1 inhibitors, short-term (≤10 min) exposure to cinobufagin did not alter ANO1 chloride channel activity and ANO1-dependent intestinal smooth muscle contraction, whereas long-term (24 h) exposure to cinobufagin significantly reduced phosphorylation of STAT3 and mRNA expression of ANO1 in CAL-27 cells. Notably, cinobufagin inhibited cell proliferation of CAL-27 cells expressing high levels of ANO1 more potently than that of ANO1 knockout CAL-27 cells. In addition, cinobufagin significantly reduced cell migration and induced caspase-3 activation and PARP cleavage in CAL-27 cells. These results suggest that downregulation of ANO1 by cinobufagin is a potential mechanism for the anticancer effect of cinobufagin in OSCC.